A simulation-based approach to perform economic evaluation scenarios. Issue 2 (1st May 2017) - Barra Montevechi, J A; da Silva Costa, R F; de Pinho, A F; de Carvalho Miranda, R
Abstract: The interest in the joint use of discrete event simulation (DES) with design of experiments (DOE), activity-based costing (ABC) and net present value (NPV) in order to aid in decision making in manufacturing systems has been on the rise in the past decade. Traditionally, the literature has presented research combining simulation with one or two of the mentioned techniques. In this paper, all four mentioned techniques are integrated into one methodology in order to economically evaluate simulation model scenarios for manufacturing systems. Scenarios are simulated and analysed through the application of ABC and DOE. Then, the significant scenarios are analysed through NPV. Through application of the methodology in a production cell, it is shown that it is viable to utilize these four techniques together. This research contributes to current literature through the development of a methodology that combines DES, ABC, DOE and NPV, in a decision-making structure.